Threat modeling with Owasp Threat Dragon & risk rating a vulnerability. (Manning Publications, 2022)
Using STRIDE and OWASP Threat Dragon, one can find the threats that impact their architecture. Once identified, you will be able to formulate the remediation and/or mitigation that can be implemented in order to provide a more secure system.